Women, the Earth, the Divine - Rae, Eleanor (Maryknoll Orbis Books, 1994)
"Eleanor Rae, co-author of Created in Her Image, weaves together three compelling topics of contemporary concern: women's identity, the environmental crisis, and the feminine divine. Women, the Earth, the Divine presents the case for rediscovering a "fe
Keywords: Feminist theology. Femininity of God. Ecofeminism. Feministische Theologie